Market expectations versus outcomes: Sectoral credit market analysis in Kenya - Caroline Kariuki; Samuel Tiriongo (Kenya Bankers Association (KBA), 2021)
This study examined the responsiveness of commercial banks' sectoral credit supply to changes in credit demand expectations, as captured in the Central Bank of Kenya's Quarterly Credit Officers Survey. The study developed an index to measure changes in credit demand expectations and subjected the index, as a regressor, to a sectoral credit supply model. Employing panel data spanning 9 sectors - agriculture, manufacturing, real estate, trade, mining & quarrying, building and construction, transport & communication, finance and insurance and households, for the period between March 2012 and March 2020, the study estimated a random-effects model of sectoral credit supply. Estimation results showed that private sectoral credit supply in Kenya increases with an increase in credit demand expectations, other factors remaining constant, while expectations of a decrease in credit demand decelerate the growth in private sector credit. The effect of expectations on actual credit outcomes is significant after a delay of 2 quarters. Based on these results, developing a clear understanding of what shapes economic agents' expectations would be instrumental in influencing commercial banks' private sector credit growth.
Keywords: 330; Kreditgeschäft; Kredit; Nachfrage; Branche; Kenia